Complete plastome sequence of Monoon laui (Merr.) B. Xue and R.M.K. Saunders, 2012: an endemic species in Hainan. Issue 9 (2nd September 2022) - Xiu, Hao; Sun, Yirong; Quan, Yunfan; Fu, Tingting; Sun, Qinghui
Abstract: Monoon laui (Merr.) B. Xue and R.M.K. Saunders 2012 is produced in Hainan province. The trunk is straight, the wood texture is straight, and the material is slightly soft, which is suitable for furniture and building materials. In our study, we report and characterize the complete plastome of M. laui The complete length of the plastome of M. laui possesses 161, 181 bp, including a large single-copy (LSC) of 89, 556 bp, small single-copy (SSC) of 18, 977 bp, and two inverted repeats (IRs) of 26, 313 bp. The overall G/C content in the plastome of M. laui is 39.13%. The plastome contains 257 genes, consisting of 130 protein-coding genes (16 of which are duplicated in the IR), 37 tRNA genes (seven of which are duplicated in the IR), and eight rRNA genes (5S rRNA, 4.5S rRNA, 16S rRNA, and 23S rRNA). Here, we explore the phylogenetic relationships and make contributions to the conservation genetics of the specie of M. laui using the complete plastome sequence.